Return of Lymantria dispar dispar (gypsy moth): A case report. (November 2021) - Haq, Mawiyah; O'Toole, Ashley; Beecker, Jennifer; Gooderham, Melinda J
An invasive moth, Lymantria dispar dispar, also known as the gypsy moth, originates from Europe and first came to Ontario, Canada, in 1969. The moth is a defoliator which feeds on oak and other deciduous trees, and less commonly, conifers. Outbreaks of Lymantria dispar dispar moth infestation occur every 7–10 years with rapid expansion of the population until there is a natural collapse due to pathogens and predators. In addition to the extensive environmental impact of defoliation of the tree canopy, the Lymantria dispar dispar moth larva (caterpillar) is responsible for causing a significant cutaneous eruption in exposed individuals. In our report, we describe six cases of Lymantria dispar dispar dermatitis which occurred in Ontario, Canada, in May of 2021. It is important for dermatologists to be aware of this potential diagnosis and to be aware of local infestation in affected areas.